Deep brain stimulation for pain - Pereira, E; Green, A; Aziz, T (2013)
Deep brain stimulation (DBS) is a neurosurgical intervention whose efficacy, safety, and utility have been shown in the treatment of movement disorders. For the treatment of chronic pain refractory to medical therapies, many prospective case series have been reported, but few have published findings from patients treated during the past decade using current standards of neuroimaging and stimulator technology. We summarize the history, science, selection, assessment, surgery, and personal clinical experience of DBS of the ventral posterior thalamus, periventricular/periaqueductal gray matter, and, latterly, the rostral anterior cingulate cortex (Cg24) in 100 patients treated now at two centers (John Radcliffe Hospital, Oxford, UK, and Hospital de São João, Porto, Portugal) over 12 years. Several experienced centers continue DBS for chronic pain with success in selected patients, in particular those with pain after amputation, brachial plexus injury, stroke, and cephalalgias including anesthesia dolorosa. Other successes include pain after multiple sclerosis and spine injury. Somatotopic coverage during awake surgery is important in our technique, with cingulate DBS considered for whole-body pain or after unsuccessful DBS of other targets. Findings discussed from neuroimaging modalities, invasive neurophysiological insights from local field potential recording, and autonomic assessments may translate into improved patient selection and enhanced efficacy, encouraging larger clinical trials. © 2013 Elsevier B.V.